Employee satisfaction model in financial service: The role of leadership style, work atmosphere, and employee enthusiasm - Farid Subkhan; Agil Permata Ramadhan (Journal of Economics and Business Letters, 2026)
Human resources are essential for augmenting labor productivity within an organizational context, including leadership style, an effective work atmosphere, employee enthusiasm, and employee satisfaction. This study aims to analyze the implications of leadership style, work atmosphere, and employee enthusiasm on employee fulfilment in the financial sector in Greater Jakarta. This study used a mixed-methods design that combined quantitative and qualitative procedures. The quantitative study involved 215 respondents from the financial services industry in Greater Jakarta. To deepen the analysis, qualitative research was conducted with ten participants from the same area. Data for the quantitative study were collected through online interviews, and for the qualitative component, through direct phone interviews. The quantitative data analysis uses SPSS version 25.0, and the statistical exercise provides empirical findings by which all instruments of the study are shown to be valid and reliable. Hypothesis evaluation was performed using multiple linear regression techniques. The qualitative part was conducted using descriptive thematic analysis. The empirical evidence of this study demonstrates that the three examined variables, leadership style, work atmosphere, and employee enthusiasm, make a substantial and favorable contribution to raising employee satisfaction, both individually and collectively. This research is crucial as a reference for developing an adaptive and agile HR management strategy to raise employee satisfaction, which leads to productivity improvement, particularly in the financial services industry.